Restoring America's neighborhoods : how local people make a difference - Greenberg, Michael R. (Rutgers University Press, 1999)
What does it take to mobilize a grass-roots force dedicated to bringing new life into a decaying neighborhood? Can any one person or group successfully halt physical deterioration, drug-related crime, or the encroachment of clusters of factories, highways, and other noxious land uses? Michael Greenberg demonstrates in this book that it can and has been done against all odds. Restoring America's Neighborhoods profiles twenty-four such cases from across the United States. It tells the story of people determined to make the blighted, crime-ridden urban enclaves in which they live and work a better place for everybody. These are people from many different walks of life: ministers working to bring jobs to their communities; city planners and federal employees trying to relocated residents of potential disaster areas; and locals taking matters into their own hands to create a healthier, more pleasing living environment for their children. Greenberg's is a heartening account of courage and unwavering resolve as well as of hope that individuals can make a difference, that violent criminals and uncaring bureaucrats need not carry the day. He calls them "streetfighters," a fitting tribute to their efforts to take back their neighborhoods, block by block and street by street. -- Provided by publisher